Guilt of a Legal Entity in an Administrative Offense in the Field of Antimonopoly Legislation - Sergei S. Sumenkov (Сибирское юридическое обозрение)
In the article, based on the comparison of different approaches to the fault of a legal entity in an administrative offense, the possibility and necessity of establishing an intentional or reckless form of guilt of a legal entity in committing an administrative offense in the field of antimonopoly legislation through the forms of fault of the respective officials are substantiated. Specific features of the “intellectual” element of guilt are applied in relation to the corresponding composition of administrative offenses. Attention is drawn to the role of antimonopoly compliance in establishing the guilt of organizations in administrative offenses in the field of antimonopoly legislation. It is proposed to introduce into the administrative law institutes of complicity, double forms of guilt and kurtosis of the executor in order to ensure proper involvement of both organizations and their officials in administrative responsibility.